2017
DOI: 10.5582/bst.2017.01087
|View full text |Cite
|
Sign up to set email alerts
|

Medical humanities play an important role in improving the doctor-patient relationship

Abstract: Doctors in China have been wounded or even killed in frequent violence as conflict between doctors and patients has intensified. China has had a massive dearth of medical students over the past decade and doctors are dissatisfied with conditions in their profession. Conditions in medicine are not conducive to medical reform. This paper notes that the main factors affecting the doctor-patient relationship are a lack of humanity in medicine, the predominance of techniques and technologies, and inappropriate admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Empathy improved the doctor-patient relationship by promoting harmonious and effective communication. Zwingmann(2017) et al found that patient-centered empathic communication can reduce patients' anxiety and negative emotions in cancer diagnosis, and increase patients' trust in doctors [39]. Relevant studies have also shown that the higher the doctor's empathy, the more cordial and warm the patients feel.…”
Section: Analysis Of the Main Resultsmentioning
confidence: 99%
“…Empathy improved the doctor-patient relationship by promoting harmonious and effective communication. Zwingmann(2017) et al found that patient-centered empathic communication can reduce patients' anxiety and negative emotions in cancer diagnosis, and increase patients' trust in doctors [39]. Relevant studies have also shown that the higher the doctor's empathy, the more cordial and warm the patients feel.…”
Section: Analysis Of the Main Resultsmentioning
confidence: 99%
“…Effective goals‐of‐care communication between medical provider and patients is associated with improved patient and family outcomes, increased clinician satisfaction and decreased healthcare costs. However, the patient–provider relationship is a complex social relationship that is affected by numerous factors, and only 20% of patient–provider disputes are caused by medical technology (Wang, Song, et al, 2017). In addition to reforming hospital administrative procedures, humanities education in medical college and on‐the‐job training are essential.…”
Section: Discussionmentioning
confidence: 99%
“…The patient–provider relationship has been a major focus of society over the past few years. The deterioration of this relationship has emerged as a highly visible risk to medical staff (Wang, Song, Zhang, & Xiao, 2017; Xiong et al, 2017). Patient–provider communication and trust have been identified as important factors in the patient–provider relationship.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the Association of American Medical Colleges is currently in the second phase of a broad project to "better delineate the current landscape of the arts and humanities in medicine and determine how best to approach a broader effort to integrate them," involving a review of current practices and the formation of a humanities "integration" committee to direct medical humanities education [3]. Proponents of the medical humanities suggest that humanistic engagement may offer a plethora of benefits to physicians and medical students, including improvements in medical acumen, deeper connections with patients and colleagues, and more personal satisfaction in the practice of medicine [1,4].…”
Section: The Medical Humanities: What They Are and Why We Need Themmentioning
confidence: 99%